Kepelbagaian kupu-kupu famili nymphalidae di Kionsom, Inanam, Sabah - Ling, Janet Wei Wei (2009)
A study on buttefly family Nymphalidae was done at the forest beside waterfall Kionsom, Inanam. The objectives of this study were to examine the diversity and composition of butterflies in the family Nymphalidae. The sampling was started from August until December 2008. Baited-trap with rotten-fruit and 'belacan' was used as the main method in this study. Aerial net was used as a supplementary method to maximize sampling data. The study of butterfly Nymphalidae was conducted for 30 days. As a result from this study, five subfamily were obtained, there are Charaxinae, Danainae, Morhinae, Nymphalinae and Satyrinae. From these five subfamilies, 35 genera, 64 species and 363 individuals were collected. The Shannon-Wiener Diversity Index, H' was 3.52, Simpsons Evenness Index (Ds) was 21.02 and Margalef Richness Index (Om) was 10.68. All the three indices showed a high diversity and composition of butterfly Nymphalidae at the forest beside waterfall Kionsom, Inanam. Nymphalinae is the most dominant subfamily which has 22 genera, 32 species and 153 individual. On the other hand subfamily is the least dominant which was Danainae has two genera, four species and seven individuals. Nympbalinae has the highest percentage of genus with 60010 and Satyrinae has the second highest percentage genus with 14.3%. Followed subfamily Morphinae and Charaxinae which show 11.4% and 8.6% respectively. Subfamily Danainae is the subfamily which has the lowest genus percentage with 5.7% only.